2015
DOI: 10.1002/ajmg.b.32395
|View full text |Cite
|
Sign up to set email alerts
|

RDoC and translational perspectives on the genetics of trauma‐related psychiatric disorders

Abstract: Individuals with a history of child abuse are at high risk for depression, anxiety disorders, aggressive behavior, and substance use problems. The goal of this paper is to review studies of the genetics of these stress-related psychiatric disorders. An informative subset of studies that examined candidate gene by environment (GxE) predictors of these psychiatric problems in individuals maltreated as children is reviewed, together with extant genome wide association studies (GWAS). Emerging findings on epigenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 140 publications
0
18
0
1
Order By: Relevance
“…Clinical studies have consistently shown reduced gray matter volume, and decreased synapses and glial cells in the mPFC of patients with anxiety and mood disorders [24,25]. In addition, preclinical studies have shown that early life stress induces changes in gene expression and structural abnormalities in the mPFC [26], as well as alterations in DNA methylation in the Brain-derived neurotrophic factor ( Bdnf ) gene, reelin gene, and genes involved in the DNA methylation regulation in the mPFC [26]. Here, we found that decreased ID3 and increased GRIN1 mRNA expression in the mPFC are associated with lower depression-like behavior as evaluated in the forced swim test.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have consistently shown reduced gray matter volume, and decreased synapses and glial cells in the mPFC of patients with anxiety and mood disorders [24,25]. In addition, preclinical studies have shown that early life stress induces changes in gene expression and structural abnormalities in the mPFC [26], as well as alterations in DNA methylation in the Brain-derived neurotrophic factor ( Bdnf ) gene, reelin gene, and genes involved in the DNA methylation regulation in the mPFC [26]. Here, we found that decreased ID3 and increased GRIN1 mRNA expression in the mPFC are associated with lower depression-like behavior as evaluated in the forced swim test.…”
Section: Discussionmentioning
confidence: 99%
“…In the second stage, this set of candidate SNPs was tested in an independent sample with respect to the phenotype of interest (i.e., AUD) at a significance threshold corrected for the number of proxy-associated SNPs. Consistent with the National Institute of Mental Health’s Research Domain Criteria (RDoC) initiative, 27 29 we considered two-dimensional measures derived from symptom scales based on self-report information: an alcohol misuse score in the ASTARRS cohorts, and a DSM-5 AUD criterion count in the Yale-Penn cohorts. Dichotomous trauma exposure was considered as interactive factor, because it was available in both cohorts.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, recent research found that neglect (as an childhood stress) can affect gene expression, DNA transcription and translation [ 54 , 55 ], which may in turn affect some genes related to depression, as described earlier.…”
Section: Discussionmentioning
confidence: 89%